Konflik Batin Tokoh Manji Film Blade of the Immortal Karya Takashi Miike_ Pendekatan Psikoanalisis Sigmund Freud - Kurniawan Yuliadmojo; Sri Oemiati (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to identify and analyze the psychological conflict experienced by the main character in Takashi Miike's film Blade of the Immortal through Sigmund Freud's psychoanalytic approach. The study focuses on three personality structures: the id, ego, and superego, which shape Manji's character as the center of his inner struggle. The research method applied is qualitative with a naturalistic descriptive approach, emphasizing the interpretation of meaning and in-depth analysis of behavior, dialogue, and visual symbols in the film. The results show that Manji faces a complex inner conflict between aggressive impulses and the desire to atone for past mistakes. The id element is reflected in the fighting instinct, anger, and the urge to kill that are difficult to control. The superego appears as a moral voice, born from guilt and the desire to protect others, especially Rin, the girl who symbolizes Manji's self-redemption. Between the two, the ego functions as a balance, guiding Manji to think rationally and transform destructive impulses into meaningful actions, such as defending the weak and upholding justice. This psychological conflict also displays the use of self-defense mechanisms, including rationalization, sublimation, and undoing, which demonstrate Manji's adaptation process to trauma and regret. The dynamics between the id, ego, and superego reflect the human struggle to find balance between instinct and morality. Research findings confirm that inner conflict is at the heart of Manji's search for meaning and redemption, allowing his psychological journey to serve as a reflection of how humans navigate urges, morality, and regret in life.